Comparación del índice de precios al consumidor de la Región Loreto con el de Lima Metropolitana periodo 2014 – 2023 - Oliveira Sanchez, Ashly Scarlett (2024)
The present research aimed to examine the behavior of Consumer Price Index (CPI) in the Loreto region compared to Lima Metropolitan during the period 2014-2023. A quantitative, non-experimental approach was employed, with a descriptive-comparative longitudinal design. The sample comprised all observations of CPI in Loreto and Lima Metropolitan during the mentioned period, collected from INEI and analyzed using descriptive statistics and variance comparison tests. The most significant results revealed a positive and significant relationship between CPIs of both regions, with an estimated coefficient suggesting a considerable influence of Lima on Loreto in terms of price variability. Confirming a differentiated behavior between Loreto and Lima's CPIs highlighted the economic interdependence between these areas. Additionally, it was found that variations in Loreto's CPI are notably higher compared to Lima's, emphasizing the need to consider these disparities in economic policy formulation and regional development strategies. These findings contribute to the understanding of economic dynamics in Peru and offer relevant insights for decision-making at both local and national levels.